A Note on the Concavity of the Mean-Variance Problem - Sibley, David (Review of Economic Studies, 1975)
Journal Article A Note on the Concavity of the Mean-Variance Problem Get access David Sibley David Sibley Yale University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 3, July 1975, Pages 479–481, https://doi.org/10.2307/2296861 Published: 01 July 1975